Management of Field Work Practices to Improve Students' Work Ability in the Office Management and Business Services Expertise Program at SMK Negeri Samarinda - Suryani, Yeni; Wijiati, Luluk; Bulantari, Dinda Ayu; Warman, Warman (ARZUSIN, 2025)
Field Work Practice (PKL) is an integral part of vocational education in Vocational High Schools (SMK) which aims to connect theory and practice to form student competencies according to the needs of the business world and the industrial world (DUDI). This study aims to evaluate the management of street vendors in the Office Management and Business Services Expertise Program at SMK Negeri Samarinda. With a qualitative approach, data is collected through in-depth interviews, observations, and documentation from students, supervisors, and industry partners. The results of the study show that although most students feel that street vendors are relevant to their field of expertise, there are still challenges in mentoring and adapting to work culture. Program evaluations tend not to involve optimal input from industry partners. Strategic recommendations include strengthening partnerships, mentor training, collaboration-based evaluation, and developing soft skills modules. With the implementation of this strategy, it is hoped that street vendor management can produce graduates who are competent and ready to compete in the world of work.